Ostomy Does Not Lead to Worse Outcomes After Bowel Resection With Ovarian Cancer: A Systematic Review - He, Xinlin; Li, Zhengyu (Frontiers in Oncology, 2022)
Background Debulking cytoreduction surgery with bowel resection is a common intervention for ovarian cancer. It is controversial whether ostomy causes worse survival outcomes and how clinical physicians should choose which patients to undergo ostomy. During this study, we performed a systematic review to determine whether ostomy leads to worse outcomes after bowel resection compared to anastomosis. We also summarized the possible indications for ostomy. Methods We searched PubMed, Embase, and Cochrane for articles containing the phrase “ovarian cancer with bowel resection” that were published between 2016 and 2021. We included studies that compared primary anastomosis with ostomy. We mainly focused on differences in the anastomotic leakage rate, length of hospital stay, overall survival, and other survival outcomes associated with the two procedures. Results and Conclusion Of the 763 studies, three were ultimately included in the systematic review (N=1411). We found that ostomy did not contribute to worse survival outcomes, and that the stoma-related complications were acceptable. Indications for ostomy require further study. Bowel resection segment margins and the distance from the anastomosis to the anal verge require consideration.